Nursing intervention within self-care with the educational support to people with type 2 diabetes mellitus - Hermelinda Ávila Alpirez; Susana Meza Guevara; Barbarita Frías Reyna; Ernestina Sánchez Andrade; Carmen Vega Alanís; María Antonia Hernández Saldivar (Universidad de Alicante, 2012)
Introduction: The purpose of this study was to determine how nursing interventions influence self-care of individuals with type 2 Diabetes mellitus, with educational support. Methodology: The design was descriptive, pre-experimental, and longitudinal. The sample was probabilistic for convenience. The sample was composed of 20 individuals with type 2 diabetes mellitus. The instrument Scale of Capacity for Self-Care was used having a Cronbach Alpha of 0.7086. Two measurements were made: one prior to the nursing intervention, the second after implementing an educational support program lasting 8 hours (2 hours per day). Measurements were made using the "paired-sample t test" to determine the difference between pre and post -test. Results: The average age was 50 to 59 years old, and the distribution by sex was predominantly female, 75%. With respect to marital status, 75% of the individuals were married. Using a "pairedsample t test" it was observed that a significant difference exists. Pre-test and post-test results show the statistical significance of nursing interventions on the capacity of self care after receiving educational support, t3.579.p.002. Discussion: Statistical significance was observed in the second measurement after nursing interventions were implemented and post-test conducted. This agrees with authors Gayosso, Oller and Agramone, and Otero who reported an increase in post test results.